AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL JAHE MERAH (Zingiber officinale var. Rubrum) TERHADAP BAKTERI Streptococcus mutans SECARA IN VITRO - Nugraha, Yogi Rahman; Sujana, Dani; Dewi, Risma Anugrah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Infections remain a major public health challenge in Indonesia, including infections of the oral cavity caused by microorganisms such as Streptococcus mutans. Red ginger is known to contain flavonoids, phenols, essential oils, and tannins that have the potential to inhibit bacterial growth. This study aims to test the antimicrobial activity of red ginger ethanol extract against Streptococcus mutans using the agar diffusion method. The results showed that at concentrations of 10 and 20%, there was a slight increase in the zone of inhibition. However, starting from 40% concentration, the increase in concentration resulted in a larger zone of inhibition. At 60% concentration, the results were close to the positive control, and at the highest concentration of 80%, the inhibition zone reached 28.04 mm with an inhibition rate of 62.24%. Overall, the inhibitory activity showed a positive relationship as the concentration of red ginger extract increased.